2015
DOI: 10.1038/srep16702
|View full text |Cite
|
Sign up to set email alerts
|

Human proximal tubule epithelial cells cultured on hollow fibers: living membranes that actively transport organic cations

Abstract: The bioartificial kidney (BAK) aims at improving dialysis by developing ‘living membranes’ for cells-aided removal of uremic metabolites. Here, unique human conditionally immortalized proximal tubule epithelial cell (ciPTEC) monolayers were cultured on biofunctionalized MicroPES (polyethersulfone) hollow fiber membranes (HFM) and functionally tested using microfluidics. Tight monolayer formation was demonstrated by abundant zonula occludens-1 (ZO-1) protein expression along the tight junctions of matured ciPTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 52 publications
3
123
2
Order By: Relevance
“…We recently successfully developed a three-dimensional bioengineered tubule system27, which we here optimized and determined monolayer integrity by analyzing paracellular diffusion prior to transport experiments. The transepithelial barrier function was measured using a custom-made flow system and inulin as a leakage marker labeled with fluorescein isothiocyanate (FITC), allowing live imaging of hollow fiber membranes (HFM).…”
Section: Resultsmentioning
confidence: 99%
“…We recently successfully developed a three-dimensional bioengineered tubule system27, which we here optimized and determined monolayer integrity by analyzing paracellular diffusion prior to transport experiments. The transepithelial barrier function was measured using a custom-made flow system and inulin as a leakage marker labeled with fluorescein isothiocyanate (FITC), allowing live imaging of hollow fiber membranes (HFM).…”
Section: Resultsmentioning
confidence: 99%
“…A number of 3D tissue engineering models have been developed that attempt to mimic the proximal tubule structure and function ((8, 16, 19, 20), for reviews see (5, 21)). A number of these systems utilize a monolayer of cells adhered to a microporous membrane coated with a thin layer of an ECM protein component, often collagen IV or laminin.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 study showed that conditionally immortalized proximal tubule epithelial cells could be seeded onto the exterior surface of hollow fibres coated with an extracellular matrix, creating biofunctionalized hollow fibres with a monolayer of cells 144 (FIG. 2e).…”
Section: Preclinical Screens Of Nephrotoxicitymentioning
confidence: 99%